The Potential Benefits of HPV E6/E7 mRNA Test in Cervical Cancer Screening in China - Zhang, Shao-Kai; Guo, Zhen; Wang, Peng; Kang, Le-Ni; Jia, Man-Man; Wu, Ze-Ni; Chen, Qiong; Cao, Xiao-Qin; Zhao, Dong-Mei; Guo, Pei-Pei; Sun, Xi-Bin; Zhang, Jian-Gong; et al. (Frontiers in Oncology, 2020)
This study aims to evaluate the clinical performance of the HPV E6/E7 mRNA test in cervical cancer screening in China. A hospital-based study was conducted with mRNA, DNA, and liquid-based cytology (LBC) as primary screening tests. Each woman with a positive result received colposcopy with lesion-targeted-biopsy. Histopathological diagnosis was used as the gold standard. The total agreement of HPV DNA and mRNA was 90.7% (95%CI: 87.9, 92.9) with a kappa value of 0.81. The positive rates of HPV DNA, mRNA, and LBC increased with the severity of histopathology diagnosis, from 25.5%, 19.1%, and 11.4% in normal to 100.0% in SCC, respectively. The sensitivities for mRNA to detect CIN2+ and CIN3+ were 93.8% (95%CI: 89.7-96.4) and 95.7% (95%CI: 91.3-97.9), respectively, which were not different from HPV DNA testing (95.7% [95%CI: 92.0-97.7], 96.3% [95%CI: 92.1-98.3]), but higher than LBC (80.4% [95%CI: 74.5-85.2] and 88.8% [95%CI: 83.0-92.8]). The specificities for mRNA to detect CIN2+ (79.0% [95%CI: 74.2-83.0]) and CIN3+ (70.5% [95%CI: 65.7-74.9]) were higher than HPV DNA testing (71.0% [95%CI: 65.9-75.7], 62.8% [95%CI: 57.8-67.5]), but lower than LBC (84.5% [95%CI: 80.1-88.0] 79.8% [95%CI: 75.4-83.6]). All tests were more effective in women older than 30 years. HPV mRNA test showed excellent agreement with the DNA test, with similar sensitivity and a higher specificity in detecting high-grade cervical lesions. It is promising that mRNA test could be used for the national cervical cancer screening to reduce false positive without losing sensitivity.